2020
DOI: 10.3390/medicina56060298
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressors—HTRA Proteases and Interleukin-12—in Pediatric Asthma and Allergic Rhinitis Patients

Abstract: Background and objective: Allergy belongs to a group of mast cell-related disorders and is one of the most common diseases of childhood. It was shown that asthma and allergic rhinitis diminish the risk of various cancers, including colon cancer and acute lymphoblastic leukemia. On the other hand, asthma augments the risk of lung cancer and an increased risk of breast cancer in patients with allergy has been observed. Thus, the relation between allergy and cancer is not straightforward and furthermore, its biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Renke et al in their work highlighted the unclear relationship between allergy and the presence of cancers, including colorectal cancer, acute lymphoblastic leukaemia, lung cancer and breast cancer [ 81 ]. In their study, they demonstrated that HtrA family protein synthesis was increased in patients with IgE-dependent allergy, but not mastocytosis [ 81 ]. Furthermore, the levels of HtrA1, HtrA2 and HtrA3 proteins did not depend on the number of mast cells but on their activity [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Renke et al in their work highlighted the unclear relationship between allergy and the presence of cancers, including colorectal cancer, acute lymphoblastic leukaemia, lung cancer and breast cancer [ 81 ]. In their study, they demonstrated that HtrA family protein synthesis was increased in patients with IgE-dependent allergy, but not mastocytosis [ 81 ]. Furthermore, the levels of HtrA1, HtrA2 and HtrA3 proteins did not depend on the number of mast cells but on their activity [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…In their study, they demonstrated that HtrA family protein synthesis was increased in patients with IgE-dependent allergy, but not mastocytosis [ 81 ]. Furthermore, the levels of HtrA1, HtrA2 and HtrA3 proteins did not depend on the number of mast cells but on their activity [ 81 ]. Considering the functions that HtrA proteins play in tumours, the results obtained by the research group demonstrate the need for further studies to determine the link between HtrA expression and the occurrence of cancer in patients diagnosed with allergy (Table 4 ) [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…To this end, increased levels of IL-12 have been already associated with allergic rhinitis in children. 31 Segboear et al have also pointed out that IL-12 could also be associated with nonallergic rhinitis to a lesser degree. 32 We also need to highlight that our rhinitis immune mechanisms' outcomes were dissimilar to previous studies on air pollution-induced CRS, showing the complexity of nasal diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, IL‐12 is produced by dendritic cells localized close to mast cells at the mucosal interface, showing a potential role of IL‐12 in atopic airway processes. To this end, increased levels of IL‐12 have been already associated with allergic rhinitis in children 31 . Segboear et al.…”
Section: Discussionmentioning
confidence: 99%